Spatial and temporal variability of precipitation concentration in Iran - Ghaedi, Sohrab; Shojaian , Ali (Geographica Pannonica, 2020)
Precipitation concentration is an important factor to assess climate hazards such as flood and availability of water resources at a regional scale. This paper investigates the spatial and temporal changes of precipitation concentration using the precipitation concentration index (PCI) in 113 stations in Iran for a duration of 30 years (1988 –2017). The results show that the mean average of the annual rainfall in Iran varies from 55 mm in the eastern and central regions (Zabol and Yazd) to 1838 mm in the southwest coast of the Caspian Sea (Bandar Anzali). The highest coefficient of variation (CV) of precipitation is related to the southeastern and southern parts of the country, whereas the lowest CV is observed in the Caspian Sea coast and northwest region. Therefore, its value is mostly a function of latitude. Precipitation concentration and its CV are also influenced by topography and reveal more homogeneity in the northern regions. The Mann-Kendall (MK) test on precipitation concentration data indicates that except for 6 stations (ascending in 2 stations and descending in 4stations), there was no significant trend in others. The stations with non-significant ascending values are located mostly in the eastern, central and western parts of the country while the non-significant descending ones can be seen in the central and northeastern regions. The results of Sen’s slope estimator are also similar to the values of the MK test.